2001
DOI: 10.1080/152873901316857752
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Status and Leptin in Basedow-Graves and Multinodular Goiter Patients

Abstract: In this study it was of interest to investigate the relationship between plasma leptin levels and thyroid function in recently diagnosed 27 Basedow-Graves patients and 22 multinodular goiter patients brought to euthyroid state with 1 mo of propylthiouracil (PTU) treatment. A group of 15 control subjects matched for age, gender, and body mass index were also studied. In Basedow-Graves patients there were significantly higher T4 and T3 levels accompanied by a marked fall in plasma thyroid-stimulating hormone (TS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
1
6
1
Order By: Relevance
“…Our data are consistent with those from Guzel et al ., in which serum levels of leptin were significantly higher in overt and subclinical hypothyroid patients 49 . Some studies found lack of change in leptin levels with thyroid dysfunction 50 51 52 53 . For instance, thyroid dysfunction was of recent onset and patients usually presented lack of change in body mass.…”
Section: Discussionmentioning
confidence: 99%
“…Our data are consistent with those from Guzel et al ., in which serum levels of leptin were significantly higher in overt and subclinical hypothyroid patients 49 . Some studies found lack of change in leptin levels with thyroid dysfunction 50 51 52 53 . For instance, thyroid dysfunction was of recent onset and patients usually presented lack of change in body mass.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of thyroid hormones decrease leptin expression in adipose tissue. But the most studies have not shown significant changes in leptin levels in hypothyroidism and hyperthyroidism disorders [36, 37]. However, increased leptin level in postpartum thyroiditis has been reported [38].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, leptin has been shown to improve hepatic and skeletal muscle sensitivity to insulin (113). In hyperthyroidism, circulating leptin levels have been found to be normal (116,118,(123)(124)(125) or decreased (115,126). Interestingly, leptin has been shown to increase peripheral type 2 deiodinase activity so that more T 3 is available to peripheral tissues (127,128); thus, leptin may play a role in raising levels of T 3 , thereby worsening hyperthyroidism (2).…”
Section: B Leptinmentioning
confidence: 97%